High-performance samarium cerium oxide electrolyte material and preparation method thereof
Synthesis of Sm0.2Ce0.8O2-δ electrolyte material through co-precipitation method, solving the problems of low conductivity and poor sintering activity at low temperatures, realizing the preparation of electrolyte materials with high-performance medium and low temperature SOFCs, and improving the conductivity and sintering activity.
Patent Information
- Application Number
- CN202411590531.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-14
AI Technical Summary
The existing CeO2-based electrolyte materials have low conductivity and poor sintering activity at low temperatures, making it difficult to meet the requirements of high-performance medium and low-temperature solid oxide fuel cells.
The Sm0.2Ce0.8O2-δ electrolyte material was synthesized by co-precipitation method, and the density and conductivity of the material were improved by controlling the reaction conditions and adding dispersants.
The preparation of high-performance samarium-cerium oxide electrolyte materials has high conductivity and sintering activity. It is suitable for medium and low temperature SOFCs, which reduces the internal resistance of the battery and improves the electrochemical performance.
Smart Images

Figure CN119447394A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an electrolyte material, in particular to a high-performance samarium-cerium oxide electrolyte material and a preparation method thereof. Background Art
[0002] Energy crisis is one of the urgent problems to be solved in today's society, and the harm it brings has seriously affected the sustainable development of human society. The development of new energy conversion and storage technologies is very beneficial to changing the existing energy structure and environmental pollution. Fuel cells, as a clean, efficient and renewable energy conversion technology, have great potential and application value in solving energy and environmental problems, and are regarded as one of the best green energy solutions. Among them, solid oxide fuel cells have the characteristics of high energy conversion efficiency, low cost, and good long-term stability, and have received widespread attention in the field of energy and environment.
[0003] Solid Oxide Fuel Cells (SOFCs) use rare earth oxides as ion-conducting electrolytes to directly convert the chemical energy of fuel into electrical energy at high temperatures. They are considered to be an efficient and clean energy conversion technology that can effectively reduce the emission of carbon dioxide and other harmful gases. However, since solid oxide fuel cells generally operate at temperatures above 800°C, their startup speed is relatively slow. Long-term high-temperature operation causes the aging rate of various fuel cell components to accelerate, which is not conducive to the commercial development of SOFCs.
[0004] In order to reduce production costs, it is particularly necessary to reduce the operating temperature of SOFCs and achieve low temperature (500-800℃). As the operating temperature of SOFCs decreases, the conductivity of the electrolyte material will also decrease, resulting in a sharp increase in the ohmic loss of the battery. Therefore, improving the conductivity of the electrolyte material itself is one of the key points in the study of key basic materials for SOFCs. In recent years, CeO2-based electrolyte materials have been widely used in low-temperature SOFCs, but since pure CeO2 is a mixed conductor that conducts oxygen ions, electrons and holes, the oxygen ion conductivity is low, so it cannot meet the requirements of high-performance SOFCs for electrolyte conductivity. In addition, CeO2 is a material that is difficult to sinter, and the densification temperature is high. The high densification sintering temperature will lead to problems such as chemical incompatibility and thermal expansion coefficient mismatch between SOFCs components. Therefore, it is very important to prepare a CeO2-based electrolyte with high conductivity and low-temperature densification sintering.
[0005] At present, there are many methods for preparing doped CeO2 electrolytes with high sintering activity. The Chinese patent with publication number CN114725461A, entitled "A low-temperature sintered densified samarium-neodymium doped cerium oxide-based barrier layer and its preparation method, solid oxide fuel cell", proposes the use of transition metal Fe and Mn sintering aids to improve the density of doped CeO2, but the doping of transition metal elements easily causes electronic conductivity, and the sintering temperature in the patent is still greater than 1250°C. The Chinese patent with publication number CN114380595A, entitled "A low-sintering temperature oxygen ion conductive ceramic material and its preparation method", the electrolyte material expression is (Ce 0.90 G 0.10 O 1.95 ) 1-x +(Fe2O3)x, wherein x is the amount of sintering aid Fe2O3 added, 0<x≤0.015. This patent aims to reduce the sintering temperature and improve the electrical conductivity by using cheap Fe2O3 as a sintering aid for GDC, but its actual sintering temperature is still above 1250°C, and the effect of improving the electrical conductivity is not ideal. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a method for preparing a high-performance samarium-cerium oxide electrolyte material. The high-performance samarium-cerium oxide electrolyte material prepared has high electrical conductivity and sintering activity, and can be used to prepare high-performance medium and low-temperature solid oxide fuel cells.
[0007] In order to solve the above technical problems, the technical solution of the present invention is:
[0008] A method for preparing a high-performance samarium cerium oxide electrolyte material comprises the following steps:
[0009] S1. Dissolve Sm(NO3)3·6H2O and Ce(NO3)3·6H2O in deionized water, then add a dispersant and mix well to obtain a mixed solution A;
[0010] S2. dissolving the precipitant in deionized water and mixing well to obtain a mixed solution B;
[0011] S3. The mixed solution A obtained in step S1 was added dropwise to the mixed solution B under stirring conditions, and stirring was continued for 2-4h after the addition was completed. After stopping stirring, aging was continued for 4-24h to obtain the reactant;
[0012] S4. The reaction product obtained in step S3 is centrifuged to obtain a precipitate 1, and the precipitate 1 is washed with anhydrous ethanol and deionized water and then centrifuged three times to obtain a precipitate 2;
[0013] S5. Dry the precipitate obtained in step S4 and then calcine it at high temperature to obtain a high-performance samarium cerium oxide electrolyte material.
[0014] Furthermore, the ratio of Sm(NO3)3·6H2O, Ce(NO3)3·6H2O, deionized water and dispersant in the present invention is (0.1-2.5) mol:(0.4-10) mol:1L:(0.2-0.5) g, and the molar ratio of Sm(NO3)3·6H2O and Ce(NO3)3·6H2O is 1:4.
[0015] Furthermore, in step S1 of the present invention, the dispersant is one or more of PVP, PEG or CTAB.
[0016] Furthermore, in step S2 of the present invention, the ratio of the precipitant to deionized water is (0.1-1) mol:1L.
[0017] Furthermore, in step S2 of the present invention, the precipitant is one or more of ammonium carbonate, oxalic acid, ammonium bicarbonate, ammonia water or urea.
[0018] Furthermore, in step S3 of the present invention, the volume ratio of the mixed solution A to the mixed solution B is 1:(2-3); the dropping speed of the mixed solution A is 5-20 mL / min; and the stirring speed is 100-500 r / min.
[0019] Furthermore, in step S4 of the present invention, the speed of each centrifugation is 6000 rpm and the time is 20 min.
[0020] Furthermore, in step S5 of the present invention, the drying temperature is 90-120° C. and the drying time is 10-12 hours.
[0021] Furthermore, in step S5 of the present invention, the high temperature calcination temperature is 550-800° C. and the time is 2-3 hours.
[0022] Another technical problem to be solved by the present invention is to provide a high-performance samarium-cerium oxide electrolyte material prepared by the above preparation method.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1) The raw materials used in the present invention are economical and safe, and the preparation process is green and environmentally friendly.
[0025] 2) In the present invention, samarium cerium oxide (chemical formula: Sm 0.2 Ce 0.8 O 2-δ ) The electrolyte material is synthesized by a simple co-precipitation method, which is low-cost, environmentally friendly, and suitable for large-scale production.
[0026] 3) The high-performance samarium cerium oxide electrolyte material prepared by the present invention has a stable structure, can be sintered at low temperature (sintering temperature is about 1150°C), has a high density, can avoid reaction with zirconium oxide-based electrolyte when used as an isolation layer, and can achieve better battery performance under low temperature conditions if used as a pure electrolyte.
[0027] 4) The high-performance samarium cerium oxide electrolyte material prepared by the present invention has excellent electrochemical properties, can show high ionic conductivity at medium and low temperatures, is conducive to ion transport, and reduces the internal resistance of the battery; as a composite electrode, it can increase the ion transport rate at the electrode three-phase interface, improve the interfacial charge transfer process of the electrode, and then improve the electrochemical properties of the oxygen electrode and the fuel electrode, and ultimately improve the battery performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The drawings described herein are used to provide a further understanding of the present invention, constitute a part of the present application, and do not constitute an improper limitation of the present invention. In the drawings:
[0029] Figure 1 The X-ray powder diffraction pattern (XRD) of the high-performance samarium-cerium oxide electrolyte material prepared in Example 1 of the present invention;
[0030] Figure 2 This is a scanning electron microscope (SEM) photograph of the high-performance samarium-cerium oxide electrolyte material prepared in Example 1 of the present invention;
[0031] Figure 3 This is the sintering curve of the high-performance samarium-cerium oxide electrolyte material prepared in Example 1 of the present invention;
[0032] Figure 4 The SEM photos of the high-performance samarium-cerium oxide electrolyte material prepared in Example 1 of the present invention sintered into ceramic sheets at different temperatures;
[0033] Figure 5 The conductivity of the high-performance samarium-cerium oxide electrolyte material prepared in Example 1 of the present invention at 400-850°C. DETAILED DESCRIPTION
[0034] The present invention will be described in detail below in conjunction with specific embodiments. The illustrative embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.
[0035] Example 1
[0036] The high performance samarium cerium oxide electrolyte material was prepared by the following steps:
[0037] S1. Dissolve Sm(NO3)3·6H2O and Ce(NO3)3·6H2O in deionized water, then add PVP and mix well to obtain a mixed solution A, wherein the ratio of Sm(NO3)3·6H2O, Ce(NO3)3·6H2O, deionized water and PVP is 0.15 mol:0.6 mol:1 L:0.2 g;
[0038] S2. Dissolve ammonium carbonate in deionized water at a ratio of 0.75 mol: 1 L and mix well to obtain a mixed solution B;
[0039] S3. The mixed solution A obtained in step S1 was added dropwise to the mixed solution B at a volume ratio of 1:2.5 under stirring at a rate of 10 mL / min, and stirring was continued for 4 h after the addition. After stopping stirring, the reaction mixture was aged for 12 h to obtain the reaction product, and the stirring speed was 400 r / min;
[0040] S4. The reaction product obtained in step S3 was centrifuged to obtain a precipitate, and the precipitate was washed with anhydrous ethanol and deionized water and centrifuged three times to obtain a precipitate, each centrifugation speed was 6000 rpm, and the time was 20 min;
[0041] S5. The precipitate obtained in step S4 is dried at 110° C. for 12 h and then calcined at 700° C. for 2 h to obtain a high-performance samarium cerium oxide electrolyte material.
[0042] Example 2
[0043] The high performance samarium cerium oxide electrolyte material was prepared by the following steps:
[0044] S1. Dissolve Sm(NO3)3·6H2O and Ce(NO3)3·6H2O in deionized water, then add PEG and mix well to obtain a mixed solution A, wherein the ratio of Sm(NO3)3·6H2O, Ce(NO3)3·6H2O, deionized water and PEG is 0.1 mol:0.4 mol:1 L:0.3 g;
[0045] S2. Dissolve oxalic acid in deionized water at a ratio of 0.1 mol:1 L and mix well to obtain a mixed solution B;
[0046] S3. The mixed solution A obtained in step S1 was added dropwise to the mixed solution B at a volume ratio of 1:2 under stirring at a rate of 20 mL / min, and stirring was continued for 2 h after the addition was completed. After stopping stirring, the reaction mixture was aged for 4 h to obtain the reaction product at a stirring rate of 500 r / min;
[0047] S4. The reaction product obtained in step S3 was centrifuged to obtain a precipitate, and the precipitate was washed with anhydrous ethanol and deionized water and centrifuged three times to obtain a precipitate, each centrifugation speed was 6000 rpm, and the time was 20 min;
[0048] S5. The precipitate obtained in step S4 is dried at 90°C for 12 hours and then calcined at 550°C for 3 hours to obtain a high-performance samarium-cerium oxide electrolyte material.
[0049] Example 3
[0050] The high performance samarium cerium oxide electrolyte material was prepared by the following steps:
[0051] S1. Dissolve Sm(NO3)3·6H2O and Ce(NO3)3·6H2O in deionized water, then add CTAB and mix well to obtain a mixed solution A, wherein the ratio of Sm(NO3)3·6H2O, Ce(NO3)3·6H2O, deionized water and PVP is 2.5 mol:10 mol:1 L:0.5 g;
[0052] S2. Dissolve ammonium bicarbonate in deionized water at a ratio of 1 mol: 1 L and mix well to obtain a mixed solution B;
[0053] S3. The mixed solution A obtained in step S1 was added dropwise to the mixed solution B at a volume ratio of 1:3 under stirring at a rate of 20 mL / min, and stirring was continued for 4 h after the addition was completed. After stopping stirring, the reaction mixture was aged for 24 h to obtain the reaction product at a stirring rate of 300 r / min;
[0054] S4. The reaction product obtained in step S3 was centrifuged to obtain a precipitate, and the precipitate was washed with anhydrous ethanol and deionized water and centrifuged three times to obtain a precipitate, each centrifugation speed was 6000 rpm, and the time was 20 min;
[0055] S5. The precipitate obtained in step S4 is dried at 120° C. for 10 h and then calcined at 800° C. for 2.5 h to obtain a high-performance samarium cerium oxide electrolyte material.
[0056] Example 4
[0057] The high performance samarium cerium oxide electrolyte material was prepared by the following steps:
[0058] S1. Dissolve Sm(NO3)3·6H2O and Ce(NO3)3·6H2O in deionized water, then add CTAB and mix well to obtain a mixed solution A, wherein the ratio of Sm(NO3)3·6H2O, Ce(NO3)3·6H2O, deionized water and CTAB is 2 mol:8 mol:1 L:0.4 g;
[0059] S2. Dissolve ammonia in deionized water at a ratio of 0.5 mol: 1 L and mix well to obtain a mixed solution B;
[0060] S3. The mixed solution A obtained in step S1 was added dropwise to the mixed solution B at a volume ratio of 1:2.4 under stirring at a rate of 5 mL / min, and stirring was continued for 3 h after the addition. After stopping stirring, the reaction mixture was aged for 20 h to obtain the reaction product at a stirring rate of 200 r / min;
[0061] S4. The reaction product obtained in step S3 was centrifuged to obtain a precipitate, and the precipitate was washed with anhydrous ethanol and deionized water and centrifuged three times to obtain a precipitate, each centrifugation speed was 6000 rpm, and the time was 20 min;
[0062] S5. The precipitate obtained in step S4 is dried at 100° C. for 11 h and then calcined at 600° C. for 3 h to obtain a high-performance samarium cerium oxide electrolyte material.
[0063] Example 5
[0064] The high performance samarium cerium oxide electrolyte material was prepared by the following steps:
[0065] S1. Dissolve Sm(NO3)3·6H2O and Ce(NO3)3·6H2O in deionized water, then add PVP and mix well to obtain a mixed solution A, wherein the ratio of Sm(NO3)3·6H2O, Ce(NO3)3·6H2O, deionized water and PVP is 0.3 mol:1.2 mol:1 L:0.2 g;
[0066] S2. Dissolve urea in deionized water at a ratio of 0.2 mol: 1 L and mix well to obtain a mixed solution B;
[0067] S3. The mixed solution A obtained in step S1 was added dropwise to the mixed solution B at a volume ratio of 1:2 under stirring at a rate of 5 mL / min, and stirring was continued for 2.5 h after the addition was completed. After stopping stirring, the reaction mixture was aged for 10 h to obtain the reaction product at a stirring rate of 100 r / min;
[0068] S4. The reaction product obtained in step S3 was centrifuged to obtain a precipitate, and the precipitate was washed with anhydrous ethanol and deionized water and centrifuged three times to obtain a precipitate, each centrifugation speed was 6000 rpm, and the time was 20 min;
[0069] S5. The precipitate obtained in step S4 is dried at 105°C for 11 hours and then calcined at 750°C for 2 hours to obtain a high-performance samarium cerium oxide electrolyte material.
[0070] Example 6
[0071] The high performance samarium cerium oxide electrolyte material was prepared by the following steps:
[0072] S1. Dissolve Sm(NO3)3·6H2O and Ce(NO3)3·6H2O in deionized water, then add PEG and mix well to obtain a mixed solution A, wherein the ratio of Sm(NO3)3·6H2O, Ce(NO3)3·6H2O, deionized water and PEG is 1 mol:4 mol:1 L:0.4 g;
[0073] S2. Dissolve ammonium carbonate in deionized water at a ratio of 0.6 mol: 1 L and mix well to obtain a mixed solution B;
[0074] S3. The mixed solution A obtained in step S1 was added dropwise to the mixed solution B at a volume ratio of 1:2.7 under stirring at a rate of 10 mL / min, and stirring was continued for 3.5 h after the addition was completed. After stopping stirring, the reaction mixture was aged for 18 h to obtain the reaction product at a stirring rate of 500 r / min;
[0075] S4. The reaction product obtained in step S3 was centrifuged to obtain a precipitate, and the precipitate was washed with anhydrous ethanol and deionized water and centrifuged three times to obtain a precipitate, each centrifugation speed was 6000 rpm, and the time was 20 min;
[0076] S5. The precipitate obtained in step S4 is dried at 115°C for 10 h and then calcined at 650°C for 3 h to obtain a high-performance samarium-cerium oxide electrolyte material.
[0077] Reference Example: The difference from Example 1 is that no dispersant PVP is added in step S1.
[0078] Comparative Example 1: Chinese patent with publication number CN114725461A.
[0079] Comparative Example 2: Chinese patent with publication number CN114380595A.
[0080] Experimental Example 1
[0081] The high-performance samarium-cerium oxide electrolyte material prepared in Example 1 was subjected to powder characterization and conductivity performance testing.
[0082] (1) The structure of the high-performance samarium cerium oxide electrolyte material was determined by powder X-ray diffractometer (CuK ray). Figure 1 As shown in the middle curve 1, the chemical formula is Sm 0.2 Ce 0.8 O 2-δ .
[0083] (2) Figure 2This is a field emission scanning electron microscope (FE-SEM, Japan Electron Scanning Electron Microscope JEOL-6701F) picture, which shows that the high-performance samarium cerium oxide electrolyte material prepared in Example 1 has a relatively uniform nano-sized flaky structure and good dispersibility.
[0084] (3) Weigh 0.5 g of the high-performance samarium-cerium oxide electrolyte material prepared in Example 1 and place it in a mold, then maintain the pressure at 4 MPa for 1 minute to press it into an electrolyte sheet.
[0085] The electrolyte sheet was placed in a muffle furnace, heated to 1150°C or 1350°C at 2°C / min, and sintered at this temperature for 5 hours to densify it. The linear shrinkage curve of the sintering process is shown in Figure 3 As shown, the SEM image of the electrolyte sheet is Figure 4 shown.
[0086] The DC four-terminal method was used to fix four wires at both ends of the electrolyte sheet with silver wire and silver paste, and the Nyquist impedance spectrum of the electrolyte in the range of 400°C-850°C was measured using an electrochemical workstation.
[0087] Substituting the fitted ohmic impedance value into formula 1, the conductivity σ of the electrolyte sheet at the corresponding temperature can be calculated. The calculation result is as follows: Figure 5 shown.
[0088]
[0089] Where A is the cross-sectional area of the electrolyte sheet (cm 2 ), L is the thickness of the electrolyte sheet (cm), and R is the ohmic resistance value of the electrolyte sheet measured.
[0090] Experimental Example 2
[0091] The density of the electrolyte materials prepared in Examples 1-6 and the reference example was measured respectively, and the density was measured by the Archimedean drainage method using anhydrous ethanol as a medium. The experimental results are shown in Table 1:
[0092] Density / % <![CDATA[Conductivity at 850 °C / S·cm -1 > Example 1 93.5 0.121 Example 2 92.8 0.106 Example 3 92.1 0.097 Example 4 94.0 0.115 Example 5 93.1 0.118 Example 6 94.1 0.118 Reference Example 87.4 0.069
[0093] Table 1
[0094] It can be seen from Table 1 that the density of Examples 1-6 of the present invention is relatively high. Some of the raw materials and preparation steps used in the reference example are different from those in Example 1. Compared with Example 1, the density of the reference example is reduced, indicating that the dispersant used in the present invention can effectively improve the density of the electrolyte material.
[0095] Experimental Example 3
[0096] The sintering temperatures of the electrolyte materials prepared in Examples 1-6, Reference Examples and Comparative Examples 1-2 were measured respectively. The sintering temperatures were measured according to the method in Experimental Example 1. The experimental results are shown in Table 2:
[0097] Sintering temperature(℃) Example 1 1150 Example 2 1150 Example 3 1150 Example 4 1150 Example 5 1150 Example 6 1150 Reference Example 1250 Comparative Example 1 1250-1300 Comparative Example 2 1250-1500
[0098] Table 2
[0099] It can be seen from Table 2 that the sintering temperatures of Examples 1 to 6 of the present invention are all lower than those of Comparative Examples 1 to 2. Some of the raw materials and preparation steps used in the Reference Example are different from those in Example 1. Compared with Example 1, the sintering temperature of the Reference Example is increased, indicating that the dispersant used in the present invention can effectively reduce the sintering temperature of the electrolyte material.
[0100] Experimental Example 4
[0101] The conductivity of the electrolyte materials prepared in Examples 1-6, the reference example and the comparative example 2 at 850° C. was measured respectively. The conductivity at 850° C. was measured according to the method in Experimental Example 1. The experimental results are shown in Table 3:
[0102] <![CDATA[Conductivity at 850 °C / S·cm -1 > Example 1 0.121 Example 2 0.106 Example 3 0.097 Example 4 0.115 Example 5 0.118 Example 6 0.118 Reference Example 0.079 Comparative Example 2 0.055-0.060
[0103] Table 3
[0104] It can be seen from Table 3 that the electrical conductivities of Examples 1-6 of the present invention at 850°C are all higher than those of Comparative Example 2. Some of the raw materials and preparation steps used in the Reference Example are different from those in Example 1. Compared with Example 1, the electrical conductivity of the Reference Example at 850°C is reduced, indicating that the dispersant used in the present invention can effectively improve the electrical conductivity of the electrolyte material.
[0105] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a high-performance samarium cerium oxide electrolyte material, characterized in that: The following steps are involved: S1. Dissolve Sm(NO3)3·6H2O and Ce(NO3)3·6H2O in deionized water, then add a dispersant and mix well to obtain a mixed solution A; S2. dissolving the precipitant in deionized water and mixing well to obtain a mixed solution B; S3. The mixed solution A obtained in step S1 was added dropwise to the mixed solution B under stirring conditions, and stirring was continued for 2-4h after the addition was completed. After stopping stirring, aging was continued for 4-24h to obtain the reactant; S4. The reaction product obtained in step S3 is centrifuged to obtain a precipitate 1, and the precipitate 1 is washed with anhydrous ethanol and deionized water and then centrifuged three times to obtain a precipitate 2; S5. Dry the precipitate obtained in step S4 and then calcine it at high temperature to obtain a high-performance samarium cerium oxide electrolyte material.
2. The method for preparing a high-performance samarium cerium oxide electrolyte material according to claim 1, characterized in that: The ratio of Sm(NO3)3·6H2O, Ce(NO3)3·6H2O, deionized water and dispersant is (0.1-2.5) mol:(0.4-10) mol:1L:(0.2-0.5) g, and the molar ratio of Sm(NO3)3·6H2O and Ce(NO3)3·6H2O is 1:
4.
3. The method for preparing a high-performance samarium cerium oxide electrolyte material according to claim 1, characterized in that: In the step S1, the dispersant is one or more of PVP, PEG or CTAB.
4. The method for preparing a high-performance samarium cerium oxide electrolyte material according to claim 1, characterized in that: In step S2, the ratio of the precipitant to deionized water is (0.1-1) mol:1L.
5. The method for preparing a high-performance samarium cerium oxide electrolyte material according to claim 1, characterized in that: In step S2, the precipitant is one or more of ammonium carbonate, oxalic acid, ammonium bicarbonate, ammonia water or urea.
6. The method for preparing a high-performance samarium-cerium oxide electrolyte material according to claim 1, characterized in that: In step S3, the volume ratio of the mixed solution A to the mixed solution B is 1:(2-3); the dropping speed of the mixed solution A is 5-20 mL / min; and the stirring speed is 100-500 r / min.
7. The method for preparing a high-performance samarium-cerium oxide electrolyte material according to claim 1, characterized in that: In step S4, the centrifugal speed is 6000 rpm and the time is 20 min each time.
8. The method for preparing a high-performance samarium-cerium oxide electrolyte material according to claim 1, characterized in that: In step S5, the drying temperature is 90-120° C. and the drying time is 10-12 hours.
9. The method for preparing a high-performance samarium-cerium oxide electrolyte material according to claim 1, characterized in that: In step S5, the high temperature calcination temperature is 550-800° C. and the time is 2-3 hours.
10. A high performance samarium cerium oxide electrolyte material prepared according to the preparation method of claims 1 to 9.
Citation Information
Patent Citations
Oxygen ion conductive ceramic material with low sintering temperature and preparation method thereof
CN114380595A
Low-temperature sintering densified samarium-neodymium doped cerium oxide-based barrier layer, preparation method thereof and solid oxide fuel cell
CN114725461A